Kajian Yuridis terhadap Penerapan Restorative Justice pada Pelajar Pelaku Tindak Pidana Tawuran Perspektif Undang-Undang Nomor 20 Tahun 2025 - Sintia Mona Pratama; Rusman Rusman; Mumuh M Rozi; Kuswandi Kuswandi (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2026)
The implementation of restorative justice for students involved in criminal acts of brawling has become an important legal issue in Cianjur Regency due to the increasing number of juvenile violence cases. Conventional criminal justice mechanisms that emphasize punishment are often considered ineffective in addressing the root causes of juvenile delinquency and may create long-term social stigma for students. This study aims to analyze the legal regulation of restorative justice for student brawl offenders under Law Number 20 of 2025, identify the obstacles encountered by the Cianjur Police in its implementation, and examine preventive measures undertaken to reduce student violence. The research employs a juridical-sociological method with a descriptive-analytical approach. Data were collected through literature studies, field observations, and interviews with relevant stakeholders involved in handling student brawl cases within the jurisdiction of the Cianjur Police. The findings indicate that restorative justice has a strong legal foundation under Law Number 20 of 2025, provided that formal and substantive requirements are fulfilled. The primary challenges are technical and situational in nature, particularly regarding the consistency of parties during mediation and the monitoring of post-agreement implementation. The study further finds that preventive and pre-emptive strategies involving schools, families, communities, and local government institutions contribute significantly to reducing student brawls. The study implies that strengthening inter-agency coordination and optimizing restorative justice mechanisms are essential to ensuring child protection, promoting social reintegration, and creating a more humane and equitable juvenile justice system.